Effects of perceived e-service quality, customer trust and e-satisfaction one-loyalty in Malaysian e-commerce industry - Ooi, Min Jie (2019)
E-loyalty is a significant influential factor to online business to capture more market share and increase profitability. The number of online store and e-business model increasing from year to year especially in this decade which caused high competitive among all the competitors. E-loyalty is to secure the business enable to survive and grow in the future. The purpose of this research is to examine the relationship and effect between perceived e-service quality, customer trust and e-satisfaction on e-loyalty in Malaysia e-commerce industry. In specific, perceived e-service quality, customer trust and e-satisfaction were used as the measurement tool to analyse the relationship and effect on e-loyalty, This data for this research was collected through survey method with 37 items in the survey questionnaire. Total of 390 respondents included in this research was randomly selected using convenient sampling technique among customers who have online purchase experience in Penang area. The study used SPSS version 22.0 to analyze the data. The findings indicate that perceived e-service quality, customer trust and e-satisfaction are significant positive relationship and effect e-loyalty. The results of this study can be used by an online store, other e-business or management to perform better in relation. The findings extend the researcher's understanding of predictors such as perceived e-service quality, customer trust and e-satisfaction that influence e-loyalty among online store in Malaysia.